1976
DOI: 10.1111/j.1600-0447.1976.tb00054.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Monoamine and Monoamine Metabolites in the Human Brain: Post Mortem Studies in a Group of Suicides and in a Control Group

Abstract: Different nuclei and regions of the brain from patients who had committed suicide and from controls were analysed for their content of monoamine and monoamine metabolites. There was a post mortem breakdown of 5-hydroxyindoleacetic acid (5-HIAA) which could be correlated to the time elapsed between the occurrence of death and autopsy. Homovanillic acid (HVA) and the monoamines did not decrease post mortem during the time observed (6-148 hours). There was no significant correlation between age and chemical varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0
2

Year Published

1977
1977
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(71 citation statements)
references
References 14 publications
4
65
0
2
Order By: Relevance
“…Ohmori et al [14] observed an increase in HVA levels in the frontal cortex of individuals who committed suicide compared to subjects who died due to physical illness. In contrast, Beskow et al [5] and Arranz et al [4] did not find any difference in HVA concentration at the level of the cortex of suicided subjects. These results have been confirmed in another study at the level of five other cerebral areas (caudate, putamen, nucleus accumbens, amygdala, hippocampus) [6].…”
Section: Introductionmentioning
confidence: 78%
“…Ohmori et al [14] observed an increase in HVA levels in the frontal cortex of individuals who committed suicide compared to subjects who died due to physical illness. In contrast, Beskow et al [5] and Arranz et al [4] did not find any difference in HVA concentration at the level of the cortex of suicided subjects. These results have been confirmed in another study at the level of five other cerebral areas (caudate, putamen, nucleus accumbens, amygdala, hippocampus) [6].…”
Section: Introductionmentioning
confidence: 78%
“…In most, but not all, studies the content of serotonin or its metabolite, 5-hydroxyindoleacetic acid (5-HIAA), is decreased in the brainstem of suicide victims (Shaw et al, 1967;Bourne et al, 1968;Pare et al, 1969;Lloyd et al, 1974;Beskow et al, 1976;Cochran et al, 1976;Korpi et al, 1986). Suicidal behavior is associated with lower levels of 5-HIAA in the CSF, and there is evidence that suicide risk can be predicted by low 5-HIAA in CSF after a suicide attempt (Nordstrom and Asberg, 1992).…”
Section: Abstract: Serotonin-1a Receptors; Dorsal Raphe Nucleus; Majmentioning
confidence: 99%
“…Although the original catecholamine hypothesis of major depression stated that a deficient NE delivery to its receptors in the CNS was one of the main causes of depression, 77 studies of NE or its metabolites in CSF, plasma, or urine, or of components of the noradrenergic system in post-mortem brain samples, reported indices suggestive of decreased, [79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96] normal, [97][98][99][100][101][102][103][104][105] or increased [106][107][108][109][110] delivery of NE to its intended receptors in the CNS or periphery. It should be noted that almost all of the prior studies of CSF NE or its metabolites in depressed patients were based on single time points.…”
Section: The Locus Ceruleus Norepinephrine Systemmentioning
confidence: 99%